1995
DOI: 10.1507/endocrj.42.69
|View full text |Cite
|
Sign up to set email alerts
|

Detection of In Situ Localization of Long Form Prolactin Receptor Messenger RNA in Lactating Rats by Biotin-Labeled Riboprobe.

Abstract: Abstract.Biotinylated riboprobe that specifically hybridized with messenger RNAs (mRNAs) encoding the long form of prolactin receptor (PRLRL) was transcribed from 269 by Hind III and Xho

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…Wild-type 129SV mammary epithelium adopted the less branched morphology of the endogenous Ragl ~'~ glands following transplant, confirming that systemic effects control this aspect of development, as recently demonstrated (Yant, 1998). Use of in situ hybridization analysis does not reveal expression of the PRLR in the mammary stromal cells of the mouse (Bera, 1994) or the rat (Meister, 1992;Ouhtit, 1993;Shirota, 1995). This suggests that prolactin is unlikely to act via the mammary stroma in rodents.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Wild-type 129SV mammary epithelium adopted the less branched morphology of the endogenous Ragl ~'~ glands following transplant, confirming that systemic effects control this aspect of development, as recently demonstrated (Yant, 1998). Use of in situ hybridization analysis does not reveal expression of the PRLR in the mammary stromal cells of the mouse (Bera, 1994) or the rat (Meister, 1992;Ouhtit, 1993;Shirota, 1995). This suggests that prolactin is unlikely to act via the mammary stroma in rodents.…”
supporting
confidence: 65%
“…Similar defects in ductal branching and end-bud differentiation are also seen in mice lacking prolactin (Horseman, 1997) or Stat5a (Liu, 1998 (Yant, 1998). Use of in situ hybridization analysis does not reveal expression of the PRLR in the mammary stromal cells of the mouse (Bera, 1994) or the rat (Meister, 1992;Ouhtit, 1993;Shirota, 1995). This suggests that prolactin is unlikely to act via the mammary stroma in rodents.…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that the failure of ductal side branching may be exerted by the mammary stroma. Although initial investigation failed to detect PRLR in the mammary stroma of the mouse or rat (Meister et al, 1992;Ouhtit et al, 1993a,b;Shirota et al, 1995), immunohistochemistry has found low levels in human breast cancer stroma using an antirat PRLR monoclonal (Reynolds et al, 1997) and through in situ hybridization (Mertani et al, 1998). Recently, the stroma of both rat (Camarillo et al, 2001) and mouse (Hovey et al, 2001) mammary gland has been shown to express PRLR.…”
Section: Ovarian Prlrs Are Required For Normal Pubertal Developmenmentioning
confidence: 99%
“…Ppp1r1b is a protein phosphatase involved in signal transduction pathways in human granulosa cells in response to dopamine and human chorionic gonadotropin stimulation [45]. Prlr encodes the prolactin receptor which is localized to granulosa cells as well as other cell types in the rat ovary [46]. Prolactin receptor expression in rat granulosa cells is increased by treatment of cultured cells with FSH, LH and hCG [47].…”
Section: Discussionmentioning
confidence: 99%